GLAUKOMA FAKOMORFIK: SEBUAH TINJAUAN PUSTAKA - Fredy Ciputra (Unram Medical Journal, 2022)
Phacomorphic glaucoma is secondary angle-closure glaucoma caused by thickening of the lens. Angle narrowing can occur slowly as cataract advances resulting in forward bowing of the iris caused by intumescent lens. Risk factors for phacomorphic glaucoma are age, gender, anterior chamber depth, axial length, and hypermetropia. Phacomorphic glaucoma is a clinical diagnosis that can be established simply by history and physical examination. Signs and symptoms experienced by patients with phacomorphic glaucoma, similar to other angle-closure glaucoma, are red eyes, pain, decreased visual acuity, increased IOP, corneal edema, anterior bowing of iris, narrow chambers and lens opacity as a sign of cataracts. The main treatment for phacomorphic glaucoma is cataract extraction, which can only be achieved after good control of IOP through drugs or laser. Early recognition of signs and symptoms of phacomorphic glaucoma and appropriate and prompt preoperative treatment greatly affect the course of surgery and the final visual outcome. Given that the COVID-19 pandemic has caused many people to delay getting their medical checkups, including cataracts checkups, the incidence of phacomorphic glaucoma may increase. This makes it important for clinicians to recognize phacomorphic glaucoma.